2019
DOI: 10.1590/0103-6440201902513
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pre-Heating Regular Resin Composites and Flowable Composites on Luting Ceramic Veneers with Different Thicknesses

Abstract: The aim of this study was to evaluate of pre-heating, filler contents and ceramic thickness on film thickness, microshear bond strength, degree of conversion and color change on ceramic veneers. Two experimental composites were prepared (Bis-GMA/UDMA/BisEMA/ TEGDMA), with different amounts of filler (65% or 50%wt) simulating a conventional and a flowable composite. The flowable (F) was used at room temperature and, the conventional either at room temperature (C) or pre-heated (CPH). Disk-shaped ceramics with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 20 publications
5
43
0
11
Order By: Relevance
“…In the present study it was observed that the prewarming of nanohybrid resin composite reduced its film thickness to be similar to the film thickness of resin cement, and it is well known that film thickness is an important factor when luting indirect restorations because thick film thickness leads to marginal misfit, allows great amount of resin material to be polymerized with great volumetric shrinkage and so high susceptibility of failure. (7) In accordance to the observations of this study, Sampaio et al (22) found that the thinner film thickness was formed by the pre-heated conventional composite, probably that occurred because temperature increased agitation of molecules and allowed mass plasticization of unpolymerized material. Moreover preheating provides a lute with a smaller coefficient of thermal expansion, with less polymerization shrinkage and with greater wear resistance at restoration margins compared to conventional resin luting cement.…”
Section: Daronch Et Alsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study it was observed that the prewarming of nanohybrid resin composite reduced its film thickness to be similar to the film thickness of resin cement, and it is well known that film thickness is an important factor when luting indirect restorations because thick film thickness leads to marginal misfit, allows great amount of resin material to be polymerized with great volumetric shrinkage and so high susceptibility of failure. (7) In accordance to the observations of this study, Sampaio et al (22) found that the thinner film thickness was formed by the pre-heated conventional composite, probably that occurred because temperature increased agitation of molecules and allowed mass plasticization of unpolymerized material. Moreover preheating provides a lute with a smaller coefficient of thermal expansion, with less polymerization shrinkage and with greater wear resistance at restoration margins compared to conventional resin luting cement.…”
Section: Daronch Et Alsupporting
confidence: 89%
“…Each ceramic plate was embedded in a wax block prior to surface treatment, in order to facilitate handling and fixation during micro-shear testing. Plates surfaces were treated with 9.5 % porcelain acid etch 7 for 60 seconds then washed for 180 seconds with air/water spray and finally dried with hot air blower in order to insure complete removal of the acid.…”
Section: Surface Treatmentmentioning
confidence: 99%
“…Metal-free ceramic restorations such as veneers, inlays, onlays, and crowns have been routinely used in clinical practice ( 1 , 2 ), mainly due to its good optical, physical, chemical, and biological properties ( 3 , 4 ). However, success of these restorations is highly dependent of an effective adhesion between ceramic, resin cement, and dental tissues ( 5 - 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Resin cement is usually the choice for bonding metal-free indirect esthetic restorations ( 3 , 4 , 8 , 9 ) and its polymerization modes can be divided in chemical, physical (light curing), and dual, which combines the desirable properties from physical and chemical activation ( 4 , 6 , 10 , 11 ). Dual system has been developed to compensate the polymerization deficiencies in attenuated light or its absence, enabling its indication in different clinical situations, resulting in superior properties compared to chemically activated cements ( 6 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation